2016
DOI: 10.1007/s00268-016-3761-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Anastomotic Leakage on Local Recurrence and Survival After Curative Anterior Resection for Rectal Cancer: A Systematic Review and Meta‐analysis

Abstract: BackgroundAnastomotic leakage is a serious complication associated with anterior resection for rectal cancer, the long-term effects of which are unclear. Therefore, a systematic review and meta-analysis were conducted to evaluate the impact of anastomotic leakage on disease recurrence and survival.MethodsWe searched PubMed, Embase, and the Cochrane Library databases from their inception to January 2016. Studies evaluating the oncologic impact of anastomotic leakage were included in the meta-analysis. Outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 53 publications
6
103
2
6
Order By: Relevance
“…A number of studies have shown that anastomotic leak is associated with increased local recurrence and reduced disease‐free survival in patients with colorectal cancer. Although this could be due to a delay in adjuvant therapy, several mechanistic theories are worthy of discussion in the context of the microbiome: implantation of exfoliated tumour cells on to the anastomotic site, metachronous carcinogenesis and inflammation‐mediated carcinogenesis.…”
Section: Anastomotic Leak and Colorectal Cancer Recurrencementioning
confidence: 99%
“…A number of studies have shown that anastomotic leak is associated with increased local recurrence and reduced disease‐free survival in patients with colorectal cancer. Although this could be due to a delay in adjuvant therapy, several mechanistic theories are worthy of discussion in the context of the microbiome: implantation of exfoliated tumour cells on to the anastomotic site, metachronous carcinogenesis and inflammation‐mediated carcinogenesis.…”
Section: Anastomotic Leak and Colorectal Cancer Recurrencementioning
confidence: 99%
“…Total mesorectal excision (TME) with sphincter preservation is increasingly offered for rectal cancer resection [1]. However, a distal rectal anastomosis is accompanied by significant risk of leakage [2] associated with increased morbidity and mortality and adverse oncological outcomes [3][4][5][6]. A diverting stoma reduces the consequences of anastomotic leakage [7][8][9][10][11][12], with loop ileostomy widely advocated as a routine part of TME procedures [13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this improved oncological outcome, nCRT followed by TME has been associated with increased postoperative surgical morbidity and decreased long‐term functional outcome. Furthermore, anastomotic leak has been associated with an increased risk of local recurrence, reduced long‐term survival and decreased disease‐free survival.…”
Section: Discussionmentioning
confidence: 99%